2014
DOI: 10.1002/pbc.25221
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 1 (PP1) and Casein Kinase II (CK2) regulate Ikaros‐mediated repression of TdT in thymocytes and T‐cell leukemia

Abstract: Background Ikaros is a DNA-binding protein that acts as master-regulator of hematopoiesis and a tumor suppressor. In thymocytes and T-cell leukemia, Ikaros negatively regulates transcription of terminal deoxynucleotide transferase (TdT), a key protein in lymphocyte differentiation. The signaling pathways that regulate Ikaros-mediated repression of TdT are unknown. Our previous work identified Casein Kinase II (CK2) and Protein Phosphatase 1 (PP1) as regulators of Ikaros DNA binding activity. Here we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Cells were cultured with or without TBB and collected for total RNA isolation. Human IKZF1 retroviral construct and retroviral production was described15174748.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were cultured with or without TBB and collected for total RNA isolation. Human IKZF1 retroviral construct and retroviral production was described15174748.…”
Section: Methodsmentioning
confidence: 99%
“…qChIP assays were performed by incubating chromatin with antibodies against Ikaros151617, H3K9me3 (Abcam, Cambridge, MA, USA) or normal rabbit IgG (Abcam) as a control15161748. Enrichment of the ChIP sample over input was evaluated by qPCR with ≥ 3 replicates using specific primers in the promoter region of DNM2 (forward: 5′-ACCGCGGGATGGAAGAG-3′, reverse: 5′-TGAAGGCGTCCTGCAGTTT-3′).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 However, Ikaros protein is expressed at high levels in most hematopoietic cells, and posttranslational modifications are hypothesized to play a critical role in regulating Ikaros activity. 19 Several groups have shown that phosphorylation, [19][20][21][22][23][24] sumoylation, 25 and ubiquitination 22 can regulate Ikaros function as a transcriptional repressor. However, the role of posttranslational modification in the regulation of Ikaros tumor suppressor activity in leukemia is unknown.…”
mentioning
confidence: 99%
“…qChIP assay was performed as reported previously [22,23]. Briefly, 2×10 7 MDA-MB-453 cells were collected by centrifugation at 2000 g for 5 min at room temperature and cross-linked in PBS containing 1% formaldehyde for 10 min on ice.…”
Section: Chromatin Immunoprecipitation(chip) and Quantitative Chip (Qmentioning
confidence: 99%